The Arabidopsis ZED1-Related Kinase Genomic Cluster Is Specifically Required for Effector-Triggered Immunity. Issue 4 (9th October 2020) - Seto, Derek; Laflamme, Bradley; Guttman, David S.; Desveaux, Darrell
Abstract : CRISPR / Cas9 - mediated deletion of an Arabidopsis gene cluster encoding eight kinases supports their immunity - specific roles in sensing pathogenic effectors .